Remote Observatories for Amateur Astronomers Using High-Powered Telescopes from Home - Hubbell, Gerald R.; Williams, Richard J.; Billard, Linda M. (The Patrick Moore Practical Astronomy Series, 2015)
Amateur astronomers who want to enhance their capabilities to contribute to science need look no farther than this guide to using remote observatories.  The contributors cover how to build your own remote observatory as well as the existing infrastructure of commercial networks of remote observatories that are available to the amateur. They provide specific advice on which programs to use based on your project objectives and offer practical project suggestions. Remotely controlled observatories have many advantages-the most obvious that the observer does not have to be physically present to carry out observations. Such an observatory can also be used more fully because its time can be scheduled and usefully shared among several astronomers working on different observing projects. More and more professional-level observatories are open to use by amateurs in this way via the Internet, and more advanced amateur astronomers can even build their own remote observatories for sharing among members of a society or interest group.